Impact of Digital Marketing Features on Consumer's Purchase Decision in High End Brand "ButtonScarves": Brand Image as a Mediator - Dexi Triadinda; Anis Fitri Nur Masruriyah (International Journal of Management Research and Economics, 2024)
The main objective of this research is to determine the influence of digital marketing on purchasing decisions. This research also aims to determine whether brand image mediates the relationship between digital marketing and purchasing decisions. The required data was obtained from a questionnaire via an online survey on Google Form. After going through responses from 45 respondents using Buttonscarves products who had made purchases on the Buttonscarves website, the data was analyzed using SEM PLS 3.0. The result is that there is a direct influence of digital marketing on brand image, but there is no significant influence of digital marketing on purchasing decisions. The results further state that brand image has a direct influence on purchasing decisions. Brand image is also able to mediate the indirect relationship between digital marketing and purchasing decisions. Theoretically, this research confirms that consumers do not immediately make purchasing decisions with digital marketing in a company, without knowledge about the brand image of the product they want to buy.